2012
DOI: 10.1179/0093469012z.00000000012
|View full text |Cite
|
Sign up to set email alerts
|

New radiometric dates for precolumbian (2000–700 b.p.) earthworks in western Amazonia, Brazil

Abstract: In this paper we present new data on the precolumbian geometric ditched enclosures identified in Acre State, western Amazonia, Brazil. Remote sensing and ground survey have revealed 281 earthworks, located mainly on the edges of high plateaus overlooking the river valleys drained by the southeastern tributaries of the Upper Purus River. Excavations have shown that the few existing cultural materials are concentrated on the slopes and in the bottoms of the ditches, as well as on small mounds that were likely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 35 publications
7
60
0
12
Order By: Relevance
“…Given that peak values of 20% for grass phytoliths and −19.7‰ for δ 13 C in surface samples (0-5 cm) represent 40-y postdeforestation, we deduce that the vegetation was never kept completely open for this length of time in the pre-Columbian era. This finding is consistent with archaeological evidence that the geoglyphs were used on a sporadic basis rather than continually inhabited (28,29). Furthermore, the absence of a charcoal peak or abrupt vegetation change 500 m away (JS2) implies that forest clearance for geoglyph construction was highly localized.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Given that peak values of 20% for grass phytoliths and −19.7‰ for δ 13 C in surface samples (0-5 cm) represent 40-y postdeforestation, we deduce that the vegetation was never kept completely open for this length of time in the pre-Columbian era. This finding is consistent with archaeological evidence that the geoglyphs were used on a sporadic basis rather than continually inhabited (28,29). Furthermore, the absence of a charcoal peak or abrupt vegetation change 500 m away (JS2) implies that forest clearance for geoglyph construction was highly localized.…”
Section: Resultssupporting
confidence: 77%
“…Excavations of the geoglyphs have shown that they were built and used sporadically as ceremonial and public gathering sites between 2000 and 650 calibrated years before present (BP), but that some may have been constructed as early as 3500-3000 BP (28)(29)(30). Evidence for their ceremonial function is based on an almost complete absence of cultural material found within the enclosed areas, which suggests they were kept ritually "clean," alongside their highly formalized architectural forms (mainly circles and squares)-features that distinguish the geoglyphs from similar ditched enclosures in northeast Bolivia (5,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This regional phenomenon has been attributed to both natural and anthropogenic drivers (Montoya and Rull, 2011;Montoya et al, 2011a,c;Rull and Montoya, 2014;Maezumi et al, 2015). Disentangling climate and pre-Columbian drivers of the late Holocene expansion of Mauritia/Mauritiella and other useful plants is complicated by the synchroneity of changes in regional climate (Baker et al, 2001b;Cruz et al, 2009;Novello et al, 2012;Wang et al, 2017) and the apex of pre-Columbian activity in lowland Amazon during this time (Roosevelt, 1999;Schaan, 2010Schaan, , 2012Gomes, 2011;Schaan et al, 2012;Stenborg et al, 2012). Paleoclimate records indicate an anti-phasing in regional precipitation patterns between the eastern Amazon and other areas of lowland South America (Baker et al, 2001b;Cruz et al, 2009;Novello et al, 2012;Wang et al, 2017).…”
Section: Pre-columbian Impact On Forest Compositionmentioning
confidence: 99%
“…Os exemplos já estudados incluem: campos elevados para agricultura (Guianas, Bolívia) (Erickson, 1980;Rostain, 2010), canais para irrigação de plantações (Venezuela) (Spencer, Redmond & Rinaldi, 1994), colinas e plataformas para moradia (Ilha de Marajó/Brasil, Equador, Bolívia) (Erickson, 2006b;Roosevelt, 1991b;Rostain, 1999;Salazar, 1998), lagos artificiais, barragens e canais para criação de peixes (Ilha de Marajó/Brasil, Bolívia) (Erickson, 2000(Erickson, , 2001Schaan, 2008, recintos monumentais formados por valetas geométricas (leste do Acre, sul do Amazonas/Brasil, Bolívia) (Erickson, 2010b;Schaan et al, 2010;Schaan et al, 2012b), valas defensivas (Alto Xingu e Amazonas central/Brasil) (Heckenberger et al, 2003;Moraes & Neves 2012), caminhos elevados (Bolívia, Venezuela) (Erickson, 2006a;Spencer & Redmond, 1998), caminhos "afundados" (Acre/Brasil, Equador) (Salazar, 1998;Schaan, 2014) e terras pretas com alto potencial agrícola (Brasil, Colômbia) (Kern et al, 2004;Mora et al, 1991;Neves et al, 2004;Woods et al, 2009)…”
Section: Modificações De Paisagens Amazônicasunclassified